2000
DOI: 10.1046/j.1439-0272.2000.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Infertility treatment in autosomal dominant polycystic kidney disease (ADPKD) - a case report

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a frequently occurring inherited condition with cysts in many organs including the kidneys. However, a combination of seminal vesicle cysts, cystic obstruction of ejaculatory duct and ADPKD is rarely encountered. The following case report presents an infertile ADPKD patient who had seminal vesicle cysts and ejaculatory duct cyst, and describes the treatment by transurethral resection of the ejaculatory duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Epididymal cysts have been reported in association with seminal vesicle cysts in adult patients with autosomal dominant polycystic kidney disease [23][24][25][26] and also in patients with seminal vesicle cysts and ipsilateral renal agenesis [16,27]. In most cases, these cysts were diagnosed radiologically with no pathological documentation and are likely to be secondary to distal obstruction of the excretory duct.…”
Section: Discussionmentioning
confidence: 99%
“…Epididymal cysts have been reported in association with seminal vesicle cysts in adult patients with autosomal dominant polycystic kidney disease [23][24][25][26] and also in patients with seminal vesicle cysts and ipsilateral renal agenesis [16,27]. In most cases, these cysts were diagnosed radiologically with no pathological documentation and are likely to be secondary to distal obstruction of the excretory duct.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors reporting an association with ADPKD describe bilateral seminal vesicle cysts, although it is not certain whether these are acquired or congenital. Marked distension of the seminal vesicles (i.e., megavesicles) is a separate entity, described previously in a small number of studies in ADPKD patients [5][6][7]13]. The majority of previous reports of seminal vesicle dilatation have been in patients presenting with hematospermia but no known ADPKD [14,15].…”
Section: Discussionmentioning
confidence: 86%
“…Dynamic evaluation of dilated seminal vesicles in men with ADPKD has only been reported by two groups [5,6]. Hendry et al found six patients with the appearance of bilateral seminal vesicle cysts in whom vasography demonstrated dilated seminal vesicles without obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 SV cysts are usually unilateral, appearing with approximately equal frequency on either side, 11 unless they are associated with APKD, in which case they are bilateral. [12][13][14][15][16][17] Danaci et al 17 found SV cysts in 27 (60%) of 45 male patients with APKD and concluded that patients with SV cysts should be evaluated for APKD. APKD is also associated with cysts in other organs such as the pancreas, spleen, and liver.…”
Section: Discussionmentioning
confidence: 99%